Identifying the attitude of pharmacy and medical studentsfor ethical principles - TEZCAN, SONGÜL (My University, 2023)
Ethics can be defined as the evaluation of moral values, human behaviors, and attitudes from good or bad or right or wrong. The regulation of professional ethics in the form of rules in order to guide the practices and behaviors of the members of the profession constitutes the ethical rules of the profession and includes the obligations of the profession towards those served. The existence of ethical decisions in health care has led to the need to determine the awareness of the students studying in the field of health sciences (medicine, dentistry, pharmacy, nursing, etc.) towards ethical principles and to determine their approaches. The aim of this study is to determine the attitudes of medical and pharmacy faculty students toward ethical principles. This cross-sectional and descriptive study was carried out at the University of Health Sciences between January and March 2023. Turkish version of the 'Scale for Attitudes of Ethical Principles' was directed to the first and last-year students of Health Sciences University Hamidiye Faculty of Medicine and Pharmacy via Google forms. As the score obtained from the scale increases (35-175), it is revealed that the awareness of the participant is high [1]. The statistical analysis is performed by SPSS 15.0 program. Cronbach Alpha internal consistency coefficient of the scale was calculated as 0.85. A total of 253 students (pharmacy n= 123, medicine n= 130) were included in our study. The difference between the total scale scores (65.33 vs 120.41) of the first and last-year medical students was found to be statistically significant (p<0.0001). Likewise, the difference between the total scale scores (60.45 vs 130.78) of the first and last-year students of the faculty of pharmacy was found to be statistically significant (p<0.0001). It was observed that there was a statistically significant and positive linear relationship at the p<0.000 level between all subdimensions of the questionnaire. A significant difference was found between the awareness of the first and last-year students of both pharmacy and medicine faculties about ethical principles. We think that one of the factors that cause this result is the increase in personal maturity during university education. We think that it would be beneficial to start courses on ethical principles at an earlier stage of the education process in all faculties, especially those in the field of health, and to include them more in the education program.
Keywords: Pharmacy; Medicine; Ethic; Scale for Attitudes of Ethical Principles